Variáveis clínicas e características de personalidade em tabagistas: implicações no desfecho do tratamento multidisciplinar - Livia Freire Ferreira (2012)
The nicotine dependence (ND) is a chronic condition, with high morbidity and mortality and has a high social cost. Interventions for smoking cessation have shown some success rate. However, few are studies that sought to investigate the psychological characteristics inherent to the patient on treatment outcomes for ND. The aim of this study was: in smokers, identify i) clinical variables that influence treatment outcomes of ND; ii) personality traits related to impulsivity that influence treatment outcomes of DN , and iii) to compare the cessation rates between the treatment group who used and did not use bupropion and / or nicotine replacement therapy. This is a non-experimental prospective research, evaluation in baseline after intervention. The patients were divided into different groups according to smoking cessation and adherence outcomes. At baseline, were applied Beck Inventories to assess symptoms of anxiety, depression and suicidal ideation and The Fargestron Test to assess severity of ND. The Barratt Impulsivity Scale (BIS) -11 and Temperament and Character Inventory - TCI, were applied to assess personality traits related to impulsivity. The psychosocial intervention followed the model proposed by the National Cancer Institute, which has The Cognitive-Behavioral Approach as its theoretical basis. The program consists of four weekly sessions in groups of 10 to 15 people, and 90 minutes of duration. At each session, were recorded presence, use or nonuse of medication and not smoking or smoking status. Only the rate of smoking cessation and adherence of patients in the fourth session was considered for analysis. The results were: i) in the Pearsons correlation, degrees of nicotine dependence were associated with impulsivity total score on BIS-11 (R ² = (0293) ² = 0.086 p = 0.03), ii) the use of bupropion and / or nicotine replacement therapy had an odds ratio = 4.06 (CI 1.1 to 14.15, p = 0.02) and effect size was moderate (Cramer's V = .314) for tobacco cessation; iii) logistic regression model parameters were not associated impulsivity with cessation or adherence outcomes (p> 0.05). We concluded that the severity of nicotine dependence is related to impulsivity and, in our study, only the use of bupropion and / or nicotine replacement therapy was predictive of success in the treatment cessation